QT dispersion, a simple tool to predict ventricular tachyarrhythmias and/or sudden cardiac death after myocardial infarction (Medical Journal of Indonesia, 2005)
Recent studies showed contradictive results of the relation between QT dispersion and the occurrence of ventricular tachyarrhythmias and/or sudden cardiac death. In addition, beta adrenoreceptors blocking agents, which are known to decrease the incidence of lethal arrhythmias after myocardial infarction, administered to the majority of patients in those studies population. Since β-blocker as secondary prevention drug was underutilized at National Cardiovascular Center Harapan Kita, this study was performed to find out the relation between QT dispersion and ventricular tachyarrhythmias and/or sudden cardiac death after previous myocardial infarction. The QT interval duration, QT dispersion and clinical variables of 36 postinfarction patients with history of sustained ventricular tachyarrhythmias and/or sudden cardiac death (event group) were compared with 75 postinfarction patients without such events (control group). QT dispersion differed significantly between study groups and was increased in the event group (115 ± 41 msec vs 81 ± 25 msec, p < 0.001). Corrected maximal QT interval duration was also prolonged in the event group (534 ± 56 vs 501 ± 35 msec, p < 0.001). Regression analysis showed that increasing QT dispersion was related to the occurrence of ventricular tachyarrhythmias and/or sudden cardiac death with OR of 3.2, 4, and 5.8 for cut-off point of 80, 90, and 100 msec respectively. The QT dispersion could predict the occurrence of ventricle tachyarrhythmias and/or sudden cardiac death in patient with AMI. This study confirmed that the QTd remain useful in free of beta blocking agents state. (Med J Indones 2005; 14: 230-6)